Node Participation Evaluation Scheme Based on Link Quality for Energy Efficient Routing in Ad-hoc Networks - Tie, Tai Hieng (2016)
Energy conservation in ad hoc network is a very important design issue and has been attracting a lot of attention in recent years.The limited energy capacity of mobile computing devices has brought energy conservation to the forefront of concerns for enabling mobile communications. This is a particular concern for ad hoc networks where devices are expected to be deployed for long periods of time with limited potential for recharging batteries. Such expectations demand the conservation of energy in all components of the mobile device to support improvements in device lifetime. The typical Ad Hoc Networks routing protocols of the Internet Engineering Task Force (IETF) are mainly the shortest path routing protocols and do not consider the energy issue. This thesis describes improvement of the conventional routing protocol by utilizing higher energy path and backup route. The aim of this paper is to design and evaluate the performance of energy aware routing protocols, called MEL-AODV (Maximum Energy Level Ad Hoc on Demand Distance Vector) and ALMEL-AODV (Alternate Link Maximum Energy Level Ad Hoc on Demand Distance Vector). Our proposed algorithms adapt the existing AODV routing protocol to select the optimal route based on the basis of the maximum energy of each route. The purpose of using energy metric as route select method is to improve the lifespan of Ad Hoc communication network and its corresponding impact on overall network performance. ALMEL-AODV routing protocol employs delaying method of RREQ flooding by considering the node's energy state. This ensures highest energy nodes are selected during path establishment. Between, intermediate nodes with energy level below predefined threshold were not chosen as forwarding node in order to prevent early route breakage and retransmission. Computer simulations using NS-2 simulator are performed with comparison to the conventional methods and the effectiveness of the proposed methods is quantitatively validated. The performance metrics used for evaluation are first dead lifetime, expiration time of connection and percentage of depleted node. From the analysis, proposed schemes provide better performance than conventional schemes especially in dense network.